BUSINESS PLAN PENGEMBANGAN LEMBAGA DAN USAHA KOPERASI SEKTOR RIIL DALAM RANGKA REVITALISASI KOPERASI NIRA SATRIA KABUPATEN BANYUMAS - Sulasih Sulasih (JBIMA (Jurnal Bisnis dan Manajemen), 2014)
Cooperative economic enterprise is an economic pillar of Indonesian society. Cooperative economic enterprise is a key in reducing poverty community members. The problems that developed in the Koperasi organization is still poor quality and lack of cooperative institutional and managerial capacity in the absence of a business plan business as a business entity. Business plan which is expected to improve the welfare of members or farmers, in order to utilize the natural resources and human resources in the region in order to optimize. Based on the statement above, the issues to be analyzed are 1) how the feasibility of the production and marketing of sugar crystals the cooperative Nira Satria Kabupaten Banyumas by analyzing the legal aspects, environmental aspects, market aspects and marketing, technical and technological aspects, aspects of management and human resources as well as financial aspects; 2) how does the business development and marketing of crystal sugar production the cooperative Nira Satria Kabupaten Banyumas; 3) how does the production of business plans and marketing sugar crystals the cooperative Nira Satria Kabupaten Banyumas. Methods of this study use descriptive method. Descriptive method is a method that aims to provide a general overview, systematic, factual and actual. This descriptive method there is two methods of descriptive qualitative and quantitative methods. Parameters measured in the business of production and marketing of sugar crystals with an emphasis on the legal aspects, the environment, markets and marketing, technical and technological, and human resources management, finance. This study used a survey method, to determine the respondents conducted by purposive sampling. Results from this study is that all aspects of the feasibility of the results showed that lead to this effort deserves to be developed and the need for a business plan and business continuity for progress production and marketing cooperative sugar crystals district becomes more advanced and developed.